Kate Ludlam: capstone - Ludlam, Kate, artist (Colorado State University. Libraries, 2015)
The artist's statement: The joy that I get out of design comes from both the creation of unique work and the atmosphere of collaboration and communication. As I move from the academic world and in to the professional one my main goal is to collaborate with a multitude of people and use my skills to communicate what they are passionate about in a way that infects viewers with a hint of that same passion. I view each new project as a story to be told, each with its own unique set of characters and settings. My style and my design sense are constantly changing, adapting to each project's purpose and to my own self-exploration. I work both with a stylus and with pen and ink.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.